Methyl jasmonate does improve postharvest conservation of ‘Golden’ papaya fruit - Ilana Urbano Bron; Rafaela Parizani Massucato; Evellyn Couto Oliveira Resende; Rogério Falheiros Carvalho; Bárbara Marçon Pereira da Silva; Patrícia Cia; Ricardo Antunes Azevedo; Angelo Pedro Jacomino (Ciência Rural, 2022)
ABSTRACT: Methyl jasmonate (MeJA) is recognized as a plant hormone that induces several biochemical changes related to improving fruit quality, but it is evident that the effect of MeJA during postharvest is very variable upon concentration, plant species, and even cultivars. The objective of this research was to relate the application of this regulator at low concentration (10 µmol L-1 for 24 h) to changes in postharvest physiology, on the incidence of anthracnose and quality of ‘Golden’ papaya fruit during storage at 24 ± 1°C. From the seventh day of storage, anthracnose incidence was reduced by more than 50% with MeJA treatment. The lesion area after infection was also reduced. Although, MeJA reduced fruit acidity, the ascorbic acid and soluble solids content were not altered during storage with the hormonal treatment. The skin color and pulp firmness showed slight retention. The reduction in ethylene production was accompanied by a reduction of respiration in treated fruits. MeJa increased CAT activity only in the skin whereas SOD activity was not induced by MeJA in both skin and pulp. Although, the increase of CAT from the third day of storage may have contributed to the reduction of lipid peroxidation in the skin, the MDA reduction in the pulp cannot be explained only by CAT activity. In summary, the application of MeJA in ‘Golden’ papaya reduced the incidence and severity of anthracnose, decreased respiration, ethylene production and lipid peroxidation. It is concluded that the application of MeJA at a low concentration (10 µmol L-1) may contribute to anthracnose control in ´Golden`papaya and slows the ripening of fruits.